The diagnostic of PAX1 gene methylation in cervical lesions and its role in the triage of non-16/18 HR-HPV positive - Chen, Meng-Meng; Zhang, Bing-Qiang; Luan, Yan-Song; Sun, Guo-Long; Zhang, Yun-Yuan; Zhou, Xiao-Yan; Zhang, Xi-Feng; Gao, Feng-Chun; Yu, Jun-Mei (Frontiers in Immunology, 2025)
ObjectiveThis study aims to systematically evaluate the application value of PAX1 gene methylation detection in cervical lesion screening and its potential advantages in the triage of non-16/18 high-risk human papillomavirus (HR-HPV) positive patients.Materials and methodsThis study enrolled 1,619 HPV-positive female patients who visited the Affiliated Hospital of Qingdao University from December 2023 to March 2025, with 989 patients ultimately meeting the inclusion criteria. All subjects underwent HPV-DNA testing, cytological examination, colposcopy, and PAX1 gene methylation detection, with results analyzed in conjunction with histopathological evaluations. HPV-DNA detection was performed using fluorescence quantitative PCR methodology capable of identifying 17 high-risk HPV genotypes. Cytological examination results were classified according to the International Society of Cytology standards. PAX1 gene methylation detection employed fluorescence quantitative PCR technology with ACTB as the internal reference gene, determining methylation levels through calculation of ΔCT values. Statistical analyses included ROC curve assessment of diagnostic performance, with intergroup comparisons conducted using one-way analysis of variance and Pearson’s chi-squared test.ResultsThe results demonstrated that PAX1 gene methylation detection showed significantly better diagnostic performance compared to cytological examination for the detection of CIN2+ and CIN3+ lesions. The AUC values for PAX1 gene methylation detection in diagnosing CIN2+and CIN3+ were 0.934 (95% confidence interval [CI]: 0.916–0.948) with sensitivity of 93.49% and specificity of 93.24%and0.875 (95% confidence interval [CI]: 0.853–0.895)with sensitivity of 95.31% and specificity of 79.77%. Among non-16/18 HR-HPV(in women positive for high-risk HPV types other than 16/18) positive patients, PAX1 gene methylation detection demonstrated higher sensitivity and specificity than cytological examination, enabling more accurate identification of patients requiring further intervention and reducing unnecessary colposcopy referrals. Furthermore, in HR-HPV positive patients with cytology results ≤ASCUS, PAX1 gene methylation detection significantly decreased colposcopy referral rates (22.29%), thus alleviating patients’ medical burden.ConclusionPAX1 gene methylation detection exhibits strong diagnostic efficiency for cervical lesions and holds significant value in triage diagnosis of non-16/18 HR-HPV positive.